Oncometabolite D-2HG drives tumor metastasis and protumoral macrophage polarization by targeting FTO/m6A/ANGPTL4/integrin axis in triple-negative breast cancer - Siyue Zhang; Ning Zhang; Tong Wan; Yinqiao He; Jie Hao; Yiwei Liu; Yidong Liu; Bing Chen; Wenjing Zhao; Lijuan Wang; Dan Luo; Chao Gao; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Background D-2-hydroxyglutarate (D-2HG), an oncometabolite derived from the tricarboxylic acid cycle. Previous studies have reported the diverse effects of D-2HG in pathophysiological processes, yet its role in breast cancer remains largely unexplored. Methods We applied an advanced biosensor approach to detect the D-2HG levels in breast cancer samples. We then investigated the biological functions of D-2HG through multiple in vitro and in vivo assays. A joint MeRIP-seq and RNA-seq strategy was used to identify the target genes regulated by D-2HG-mediated N6-methyladenosine (m6A) modification. RNA pull-down assays were further applied to identify the reader that could specifically recognize the m6A modification on angiopoietin like 4 (ANGPTL4) mRNA and RNA immunoprecipitation was used to confirm the findings. Results We found that D-2HG accumulated in triple-negative breast cancer (TNBC), exerting oncogenic effects both in vitro and in vivo by promoting TNBC cell growth and metastasis. Mechanistically, D-2HG enhanced global m6A RNA modifications in TNBC cells, notably upregulating m6A modification on ANGPTL4 mRNA, which was mediated by the inhibition of Fat-mass and obesity-associated protein (FTO), resulting in increased recognition of m6A-modified ANGPTL4 by YTH N6-methyladenosine RNA binding protein F1 (YTHDF1), thereby promoting the enhanced translation of ANGPTL4. As a secretory protein, ANGPTL4 subsequently activated the integrin-mediated JAK2/STAT3 signaling cascade in TNBC cells through autocrine signaling. Notably, the knockdown of ANGPTL4 or treatment with GLPG1087 (an integrin antagonist) significantly reduced D-2HG-induced proliferation and metastasis in TNBC cells. Additionally, ANGPTL4 was found to promote macrophage M2 polarization within the tumor microenvironment via paracrine signaling, further driving TNBC progression. The association of ANGPTL4 with poor prognosis in TNBC patients underscores its clinical relevance. Conclusions Our study unveils a previously unrecognized role for D-2HG-mediated RNA modification in TNBC progression and targeting the D-2HG/FTO/m6A/ANGPTL4/integrin axis can serve as a promising therapeutic target for TNBC patients.